2016
DOI: 10.1080/15226514.2016.1156638
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a suitable plant for phytoremediation in mining artisanal zones

Abstract: A study was undertaken with the aim of identifying a suitable plant for the phytoremediation of metal-polluted soil from an artisanal mining area in Ecuador. Three zones including a natural zone (NZ), abandoned zone (AZ) and intensively mined zone (IZ) were selected. Three common native plants grown in the three zones were identified and collected, including Miconia zamorensis, Axonopus compressus and Erato polymnioides. The percentage of arbuscular mycorrhizal colonization that benefits their own survival in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
8
12
0
Order By: Relevance
“…Marrugo-Negrete et al [5], presented for Clidemia sp. Hg concentrations in their tissues (Root: 0.23 mg kg −1 , Stem: 0.11 mg kg −1 , Leaves: 0.22 mg kg −1 ) results similar to those obtained in T2 and T3; and Chamba et al [42], for M. zamorensis showed high Pb concentrations in root: 379 mg kg −1 , stem: 67 mg kg −1 and leaves: 68 mg kg −1 , higher than our study, and Cd concentrations in root (2.8 mg kg −1 ), stem (0.89 mg kg −1 ) and leaves (0.80 mg kg −1 ), similar to those obtained for leaves and stem in our study.…”
Section: Concentration Of Hg Pb and CD In Plant Tissues And Phytoreme...supporting
confidence: 83%
See 2 more Smart Citations
“…Marrugo-Negrete et al [5], presented for Clidemia sp. Hg concentrations in their tissues (Root: 0.23 mg kg −1 , Stem: 0.11 mg kg −1 , Leaves: 0.22 mg kg −1 ) results similar to those obtained in T2 and T3; and Chamba et al [42], for M. zamorensis showed high Pb concentrations in root: 379 mg kg −1 , stem: 67 mg kg −1 and leaves: 68 mg kg −1 , higher than our study, and Cd concentrations in root (2.8 mg kg −1 ), stem (0.89 mg kg −1 ) and leaves (0.80 mg kg −1 ), similar to those obtained for leaves and stem in our study.…”
Section: Concentration Of Hg Pb and CD In Plant Tissues And Phytoreme...supporting
confidence: 83%
“…at T0 and T1. Chamba et al [ 42 ] reported for M. zamorensis BCF (Pb: 0.24–0.59 and Cd: <0.06–1.01) and TF (Pb: 0.17–0.19 and Cd: <0.05–0.29) values, similar TF > 0.1 for Cd in the four treatments, similar TF for Pb at T2, and similar BCF (1.01) to T1 for Cd. Demonstrating that the accumulation and translocation capacity of these metals are presented in different proportions, depending on the concentration and bioavailability of metals, physicochemical characteristics of the soil such as pH and OM content, in addition to the cellular mechanisms of plants to avoid or tolerate the absorption of metals [ 113 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioconcentration factor ( BCF ) was obtained for the roots using Equation (2) [ 39 , 44 , 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Faced with this problem, finding innovative research to eliminate, replace, or reduce environmental pollution in mineral processing is standard. Some examples are the cyanide phytoremediation by water hyacinths (Eichhornia crassipes) in the cyanide effluents treatment in small-scale gold mining [253], hyperaccumulation of zinc by Corydalis davidii in Zn-polluted soils [254], Erato polymnioides as a phytoremediation plant for soils contaminated with Pb, Zn, Cu, and Cd [255], and Heliconia psittacorum in remediating soils and water polluted with heavy metals [256].…”
Section: Cluster 2 (Blue Colour): Asm Environmental Impactsmentioning
confidence: 99%